1994
DOI: 10.7164/antibiotics.47.1417
|View full text |Cite
|
Sign up to set email alerts
|

Bioxalomycins, new antibiotics produced by the marine Streptomyces sp. LL-31F508. Taxonomy and fermentation.

Abstract: An actinomycete strain designated LL-3 1F508 was isolated from an intertidal sediment sample collected in Key West, Florida. Culture LL-31F508 was assigned to the Streptomyces genus based on the presence of LL-diaminopimelic acid (DAP)in the cell wall and observations of spiny spores using scanning electron microscopy (SEM). Excellent antimicrobial activity against Staphyloccoccus and Enterococcusspp. weredetected in both the supernatant and cell extract samples from fermentations of culture LL-31F508. Product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(42 citation statements)
references
References 10 publications
2
39
0
1
Order By: Relevance
“…The cell wall chemistry of the Streptomyces spp. has also been reported by several researchers [23][24]. In the present study, S. parvulus DOSMB-D105 was investigated for the cell wall amino acids and whole cell sugars.…”
Section: Cell Wall Chemistrysupporting
confidence: 66%
See 2 more Smart Citations
“…The cell wall chemistry of the Streptomyces spp. has also been reported by several researchers [23][24]. In the present study, S. parvulus DOSMB-D105 was investigated for the cell wall amino acids and whole cell sugars.…”
Section: Cell Wall Chemistrysupporting
confidence: 66%
“…Growth response of the organism to the inhibitory compounds was studied and it was found that the isolate could tolerate crystal violet, sodium aside and sodium chloride. Likewise, other researchers have reported the tolerance of actinobacteria to inhibitory compounds [24,29]. S. parvulus DOSMB-D105 was sensitive to gentamycin, clindamycin and amikacin and resistant to cepholothin, co-trimoxale, ofl axin and penicillin as observedin Streptomyces spp.…”
Section: Physiological Characteristics Of S Parvulus Dosmb-d105mentioning
confidence: 79%
See 1 more Smart Citation
“…Since environmental conditions of the sea are extremely different from terrestrial conditions, they produce different types of antibiotics. Several antibiotics have been isolated from marine actinobacteria by many researchers [20][21][22][23][24][25][26][27][28][29][30] . The isolated antibiotics are entirely new and unique when compared to those from the terrestrial ones 31 .…”
Section: Biotechnological Importance Of Marine Actinobacteriamentioning
confidence: 99%
“…Culture LL-31F508 was isolated from an intertidal soil sample collected in Key West, Fla., and was identified as Streptomyces viridodiastaticus subsp. "litoralis" (1). Chemical analyses of fermentation broths revealed the presence of a novel antibiotic complex, the bioxalomycins (18,22).…”
mentioning
confidence: 99%